IMF Staff papers : Volume 12 No. 3. (IMF Staff Papers; IMF Staff Papers, 1965)
Selections from this paper were delivered at the Annual Meeting of the American Statistical Association, Philadelphia, Pennsylvania, on September 8, 1965.